Il corpo nelle esperienze di disastro e attivismo in siti contaminati dall’amianto - Agata Mazzeo (Archivio Antropologico Mediterraneo)
This article focuses on the centrality of the body in the experiences of disaster and activism in two asbestos-contaminated sites in Italy and Brazil. Asbestos-related disasters appear and reveal their impact primarily through the body of the exposed person who experiences the symptoms of the diseases caused by the inhalation of the carcinogenic fibres of asbestos minerals. Then, the “natural”, social and corporeal, being-in-the-world of a person is upset. However, the contaminated body is not only the place where the disaster becomes violently evident, but it is also the place of a memory since it preserves the traces of such disasters, which often remain invisible. The body acts as a tool of knowledge and struggle through the language and the practices of activism. From the embodied suffering then a new knowledge and new practices emerge that give concreteness to objectives of social justice, in the daily life of the exposed and survivors.